A influência do sistema rodoviário no processo de urbanização de Feira de Santana-Bahia - CERQUEIRA, Eufrosina de Azevêdo (2015)
The urban concentration growing in increasingly gigantic agglomerations, the massive intervention of the State in the production of collective equipment and the struggles in urban function of social inequalities, are factors that interfere with the analysis of the urban process the cities go through. Feira de Santana, the second largest city of Bahia, is one of the examples of this pattern of urbanization challenging for the government. The configuration of its urban development is founded on popular fairs, what made it become the largest commercial center in the interior of Bahia. Its spatial organization is directly related to cattle trade and livestock, activities which have contributed to its growth and interfered directly with the process of urbanization. The fact that it is considered as the largest trunk road from the North and Northeast, and the second largest in the country, allows the circulation within the road area, both national and regional levels, causing Feira de Santana town to function as the axis of convergence. The objective of this work was to evaluate the factors that have contributed to the acceleration to the expansion of Feira de Santana urbanization through the influence of the road system. To meet the proposed objective a bibliographic survey was carried out on the urban planning and transport. Then it was done the characterization of Feira de Santana town describing its process of urbanization since its origin to the present day. The field research was carried out based on data collection obtained through interviews, which were analyzed with the use of computational tool, the software NVivo. To attend the proposed objective it was part of the analyzes conducted a descriptive study of editions of Directors Plans and contextualization of urban expansion, with the use of photographs. 100% of the interviewed people confirmed that the trunk road was a key factor in the process of urbanization of Feira de Santana town. The analysis of this expansion, through the use of photographic records, also contributed to assure that, for its geographical location, and its road system, the town has expanded in all directions. The public politic adopted by their Legal Instruments denoted the urban expansion has already been considered since the 1970s, when the mayor requested that its first Master Plan, composed in 1968, was re-evaluated. On the basis of the analyzes it comes to conclusion that the road system influenced the process of urbanization of Feira de Santana contributing vigorously to this process, making the original village become a Metropolitan Region.